Loss of Catecholaminergic Neuromodulation of Persistent Forms of Hippocampal Synaptic Plasticity with Increasing Age - Twarkowski, Hannah; Manahan-Vaughan, Denise (Frontiers in Synaptic Neuroscience, 2016)
Neuromodulation by means of the catecholaminergic system is a key component of motivation-driven learning and behaviorally modulated hippocampal synaptic plasticity. In particular, dopamine acting on D1/D5 receptors and noradrenaline acting on beta-adrenergic receptors exert a very potent regulation of forms of hippocampal synaptic plasticity that last for very long-periods of time (>24h), and occur in conjunction with novel spatial learning. Antagonism of these receptors not only prevents long-term potentiation (LTP) and long-term depression (LTD), but prevents the memory of the spatial event that, under normal circumstances, leads to the perpetuation of these plasticity forms. Spatial learning behavior that normally comes easily to rats, such as object-place learning and spatial reference learning, becomes increasingly impaired with aging. Middle-aged animals display aging-related deficits of specific, but not all, components of spatial learning, and one possibility is that this initial manifestation of decrements in learning ability that become manifest in middle-age relate to changes in motivation, attention and/or the regulation by neuromodulatory systems of these behavioral states. Here, we compared the regulation by dopaminergic D1/D5 and beta-adrenergic receptors of persistent LTP in young (2-4 month old) and middle-aged (8-14 month old) rats. We observed in young rats, that weak potentiation that typically lasts for ca. 2h could be strengthened into persistent (>24h) LTP by pharmacological activation of either D1/D5 or beta-adrenergic receptors. By contrast, no such facilitation occurred in middle-aged rats. This difference was not related to an ostensible learning deficit: a facilitation of weak potentiation into LTP by spatial learning was possible both in young and middle-aged rats. It was also not directly linked to deficits in LTP: strong afferent stimulation resulted in equivalent LTP in both age groups. We postulate that this change in catecholaminergic control of synaptic plasticity that emerges with aging, does not relate to a learning deficit per se, rather it derives from an increase in behavioural thresholds for novelty and motivation that emerge with increasing age that impact, in turn, on learning efficacy.